2012
DOI: 10.4067/s0716-10182012000100008
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas spp asociada a enfermedad diarreica aguda en Cuba: estudios de casos y controles

Abstract: Aeromonas spp asociated to acute diarrheic disease in Cuba: case-control studyThe members of the genus Aeromonas are currently considered important gastrointestinal pathogens in different geographical areas. From February 1985 to January 2005 several case-control studies were coordinated by the National Reference Laboratory for Diarrheal Diseases from the Pedro Kouri Institute. The study purpose was to analyze a possible pathogenic role for Aeromonas spp in Cuban children with acute diarrhea. In that period 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Gastroenteritis caused by Aeromonas is a problem among the pediatric population, occuring mainly in children under three years with an incidence between 2.3% and 13% in countries like Taiwan and Nigeria, respectively [3,196]. However, studies by Bravo et al [197] and Mansou et al [194] showed a 7.5% and 1.4% incidence of Aeromonas children's diarrhea, respectively, in Spain. Between 2-20% of gastroenteritis cases are monomicrobial and only 0-2% of children are asymptomatic carriers [198]; the diarrhea might last for one or two weeks and feces shows a liquid consistency [5,196].…”
Section: Gastroenteritismentioning
confidence: 99%
“…Gastroenteritis caused by Aeromonas is a problem among the pediatric population, occuring mainly in children under three years with an incidence between 2.3% and 13% in countries like Taiwan and Nigeria, respectively [3,196]. However, studies by Bravo et al [197] and Mansou et al [194] showed a 7.5% and 1.4% incidence of Aeromonas children's diarrhea, respectively, in Spain. Between 2-20% of gastroenteritis cases are monomicrobial and only 0-2% of children are asymptomatic carriers [198]; the diarrhea might last for one or two weeks and feces shows a liquid consistency [5,196].…”
Section: Gastroenteritismentioning
confidence: 99%